Dihomo-gamma-linolenic acid induces fat loss in C. elegans in an omega-3-independent manner by promoting peroxisomal fatty acid β-oxidation12. Issue 3 (21st February 2018) - Navarro-Herrera, David; Aranaz, Paula; Eder-Azanza, Laura; Zabala, María; Hurtado, Cristina; Romo-Hualde, Ana; Martínez, J. Alfredo; González-Navarro, Carlos J.; Vizmanos, José L.
Abstract : Omega-6 fatty acids might induce beneficial effects on body fat-content and metabolism. Abstract : Bioactive compounds, including some fatty acids (FAs), can induce beneficial effects on body fat-content and metabolism. In this work, we have used C. elegans as a model to examine the effects of several FAs on body fat accumulation. Both omega-3 and omega-6 fatty acids induced a reduction of fat content in C. elegans, with linoleic, gamma-linolenic and dihomo-gamma-linolenic acids being the most effective ones. These three FAs are sequential metabolites especially in omega-6 PUFA synthesis pathway and the effects seem to be primarily due to dihomo-gamma-linolenic acid, and independent of its transformation into omega-3 or arachidonic acid. Gene expression analyses suggest that peroxisomal beta oxidation is the main mechanism involved in the observed effect. These results point out the importance of further analysis of the activity of these omega-6 FAs, due to their potential application in obesity and related diseases.